2014
DOI: 10.1007/s00334-014-0453-3
|View full text |Cite
|
Sign up to set email alerts
|

Models of wetland settlement and associated land use in South-West Germany during the fourth millennium b.c.

Abstract: A GIS-based modelling approach is presented that interprets existing data on subsistence strategies of pile-dwelling people of the Lake Constance area in SouthWestern Germany and NorthEastern Switzerland. This is conducted using the examples of the settlement sites at Hornstaad-Hörnle 1, Sipplingen-Osthafen and Degersee 1. Soil distribution and the geomorphologic features of a landscape are used as the basis for illustrating various scenarios of land use depicting hypotheses of economic strategies and aspects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…The particularly low δ 15 N values of plants growing in recently cleared woodland are likely due to acidic soils (pH 4-6 for the experimental plots), which inhibit ammonia loss (Nadelhoffer & Fry 1994), and low rates of nitrogen cycling in forest soils due to lack of disturbance (Mariotti et al 1980;Hobson 1999). It is also unfeasible that denitrification caused by waterlogging is the cause of the high δ 15 N values, since plants indicative of wet growing conditions are not prevalent among the crop weeds (Maier 1999;Stika 2009;Fischer et al 2010) and soil surveys in the vicinity of all of the sites have revealed well-drained soils that would have been suitable for agriculture (Maier 1999;Fischer et al 2010;Baum 2014). It is therefore most likely that the relatively high cereal grain δ 15 N values are due to addition of 15 N-enriched manure/organic matter.…”
Section: Crop Cultivationmentioning
confidence: 99%
“…The particularly low δ 15 N values of plants growing in recently cleared woodland are likely due to acidic soils (pH 4-6 for the experimental plots), which inhibit ammonia loss (Nadelhoffer & Fry 1994), and low rates of nitrogen cycling in forest soils due to lack of disturbance (Mariotti et al 1980;Hobson 1999). It is also unfeasible that denitrification caused by waterlogging is the cause of the high δ 15 N values, since plants indicative of wet growing conditions are not prevalent among the crop weeds (Maier 1999;Stika 2009;Fischer et al 2010) and soil surveys in the vicinity of all of the sites have revealed well-drained soils that would have been suitable for agriculture (Maier 1999;Fischer et al 2010;Baum 2014). It is therefore most likely that the relatively high cereal grain δ 15 N values are due to addition of 15 N-enriched manure/organic matter.…”
Section: Crop Cultivationmentioning
confidence: 99%
“…Agents in WELASSIMO are: "households", comprising of an averaged 6 inhabitants; individual heads of livestock; secondary forest patches (age < 50 years); primary forest patches (age > 50 years); cereal field patches. For the formulation of the agent´s internal specifications and the necessary calculations, I reverted mainly on the published palaeoecological and archaeological data on wetland sites in the North-Western pre-alpine forelands of the 4 th Millennium BC which I have compiled in [16]. The landscape is represented through grid cells of 25x25 m. Each cell incorporates a set of attributes, which are derived from modern spatial data and are modulated according to paleoenvironmental data on forest cover and soil development.…”
Section: The Modelmentioning
confidence: 99%
“…As an example of these models, Baum (2014) has formalized a GIS-based object model based on information from available and relevant literature and local archaeological data regarding environmental characteristics (soil, vegetation, local climate, distance to village) and cropping and livestock-keeping practices, to evaluate the environmental impact of human settlements over several village territories, along several farming scenarios (shifting, intensive garden and non-intensive cultivation) and diet assumptions. (Figure 1) Fig.…”
Section: Tem ("Terroir"-based Environmentally Constrained Modelsmentioning
confidence: 99%
“…(Figure 1) Fig. 1:Three "snapshot models" illustrating the model design in (Baum 2014). Economic areas are calculated using various hypotheses and their extent modeled in a GIS.…”
Section: Tem ("Terroir"-based Environmentally Constrained Modelsmentioning
confidence: 99%
See 1 more Smart Citation